Geochemical and sedimentological record of sediment core ETL-C3 retrieved from Ea Tyn Lake (Central Highlands, Vietnam) - Ingmar Unkel; Thái Nguy?n-ình; D??ng Nguy?n-Thùy; Antti E K Ojala; Arndt Schimmelmann; H??ng Nguy?n-Văn (PANGAEA, 2023)
In March 2020, two parallel sediment cores ETL-C3 and ETL-C4 (12.38589°N, 107.95399°E) were recovered from Ea Tyn Lake (Vietnam) using a Livingston/Bolivia-style customized piston corer. The cores represent sequences of 1-m segments with a vertical offset of ~50 cm between cores to ensure a complete record without gaps between successive segments. The two cores were visually correlated based on marker layers producing an ETL master sequence with a total length of 877 cm (sedimentary units 1-14). The core was scanned at 1 cm resolution with an Avaatech X-ray Fluorescence (XRF) core scanner and the raw data presented here is displayed as element counts per second (cps). RGB colour values were taken with a digital line scan camera to depict colour variation with depth. RGB colors were tranformed into the CIELAB color space using convertColor in the R-package grDevices. Principal component analysis (PCA) was performed using the basic-R function prcomp. The chronology is based on 12 AMS radiocarbon (14C) dates derived from plant macrofossils and measured at the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility. The age-depth-model was produced based on the 12 14C dates and 4 137Cs dates using the R-package rbacon. The core sequence covers the last 1250 years cal BP and reflects long-term monsoon variability (Rb/Sr ratio) and drought events (PC2) in the throughout the respective time window of the core.